Takotsubo Cardiomyopathy Associated with Primary Hyperthyroidism Secondary to Toxic Multinodular Goiter - Murdoch, Dale; O'Callaghan, William; Reda, Elham; Niranjan, Selvanayagam (International Journal of Angiology, 2016)
Takotsubo cardiomyopathy is increasingly recognized as a distinct clinical entity. An association with thyroid disease has been identified in several case reports, mostly in the context of Grave disease. We report the case of a 67-year-old woman presenting with takotsubo cardiomyopathy and thyrotoxicosis secondary to toxic multinodular goiter. Previously unreported, this suggests that this association is related to the direct effects of thyroid hormone, rather than an autoimmune mechanism. Thyroid disease should be considered in patients presenting with takotsubo cardiomyopathy.
Keywords: takotsubo; cardiomyopathy; hyperthyroidism; toxic multinodular goiter